Association between Commensal Bacteria and Opportunistic Pathogens in the Dental Plaque of Elderly Individuals - Al Gebouri, Dr. Hanan Selman Hessan (American Journal of Biology and Natural Sciences, 2025)
The prevalence of systemic disease may rise in older adults with opportunistic mouth infections. Investigating the variations in oral bacterial ecology between independent elderly (community-dwelling residents) and dependent elderly (inpatients) was The rationale of this analysis was to find the incidence of α-hemolytic streptococci (p < 0.001) and Neisseria types (p = 0.004) was significantly lower in hospitalized individuals when compared with community dwellers after multiple confounders were adjusted. In contrast, they showed a higher detection frequency of Significant detection rates were observed for Pseudomonas aeruginosa (p = 0.024) MRSA (p = 0.011) and Actinomyces organisms (p = 0.005) among bacterial isolates. Increased need for intensive care among hospitalized patients were significantly associated with MRSA (p = 0.004) and P. aeruginosa (p = 0.018), but inversely related to α-streptococci. Patients on enteral nutrition by feeding tube were significantly less likely to be positive for streptococci (p = 0.041) and significantly more likely to have Pseudomonas aeruginosa (p = 0.004) than those in whom feeding tubes were not necessary. Similarly, α-streptococci were significantly less recovered from inpatients with history of previous antimicrobial therapy (p = 0.049) and MRSA more detectable (p = 0.007) that those without history. After adjustment for age and sex, inpatients who were negative for α-streptococci were more commonly detected with P. aeruginosa (p = 0.006) and MRSA (p = 0.001), in comparison to those colonised with oral α-streptococci. In conclusion, the detection of α-streptococci in the oral microbial flora was negatively correlated with MRSA and P. aeruginosa colonisation, and it may serve as an indicator of the oral microbial dysbiosis and a potential pathogenic colonisation.